Investigations of the process of oxidation of polyethylene film, modified with high energy electron beam, using infrared spectroscopy and photoelectron spectroscopy methods - Żenkiewicz, M.; Rauchfleisz, M.; Czupryńska, J. (Polimery, 2022)
Possibilities of application of infrared spectroscopy in polymers investigations were presented. The results of authors' research work on low density polyethylene (PE-LD) film oxidation, under the influence of high energy electron beam, have been presented. Fourier transformation infrared spectroscopy (FT-IR) (Figs. 1-4) and X-ray photoelectron spectroscopy (XPS) (Figs. 5-8) were used for estimation of PE- LD chemical structure changes occurring as a result of the process discussed. It has been stated that an oxidation degree of PE-LD film (the bulk oxidation as well as surface oxidation) increases with an increase of radiation dose. Oxidation degree of polymer surface is over fourteen times higher in case of the film modified with 280 kGy dose than for unmodified film (Fig. 9). The oxygen, combined in this process, occurs mainly in ketone, aldehyde, acidic and ester groups. An increase of radiation dose causes the increasing of number of various types of carbon and oxygen atoms bonds.